NAP counteracts hyperglycemia/hypoxia induced retinal pigment epithelial barrier breakdown through modulation of HIFs and VEGF expression. Issue 2 (28th September 2017) - D'Amico, Agata G.; Maugeri, Grazia; Rasà, Daniela M.; La Cognata, Valentina; Saccone, Salvatore; Federico, Concetta; Cavallaro, Sebastiano; D'Agata, Velia
Abstract : Diabetic macular edema (DME) is a common complication leading to a central vision loss in patients with diabetes. In this eye pathology, the hyperglycaemic/hypoxic microenvironment of pigmented epithelium is responsible for outer blood retinal barrier integrity changes. More recently, we have shown that a small peptide derived from the activity‐dependent neuroprotective protein (ADNP), known as NAP, counteracts damages occurring during progression of diabetic retinopathy by modulating HIFs/VEGF pathway. Here, we have investigated for the first time the role of this peptide on outer blood retinal barrier (BRB) integrity exposed to hyperglycaemic/hypoxic insult mimicking a model in vitro of DME. To characterize NAP role on disease's pathogenesis, we have analyzed its effect on HIFs/VEGF system in human retinal pigmented epithelial cells, ARPE‐19, grown in high glucose and low oxygen tension. The results have shown that NAP prevents outer BRB breakdown by reducing HIF1α/HIF2α, VEGF/VEGFRs, and increasing HIF3α expression, moreover it is able to reduce the percentage of apoptotic cells by modulating the expression of two death related genes, BAX and Bcl2. Further investigations are needed to determine the possible use of NAP in DME treatment. Abstract : NAP counteracts damages occurring during progression of diabetic retinopathy by modulating HIFs/VEGF pathway NAP prevents outer BRB breakdown by reducing HIF1α/HIF2α and HIF3α expression.